Molecular dynamics simulation on the allosteric analysis of the c‐di‐GMP class I riboswitch induced by ligand binding. Issue 1 (23rd July 2018) - Li, Chaoqun; Zhao, Xiaojia; Xie, Pengtao; Hu, Junping; Bi, Huimin
Abstract: Riboswitches are RNA molecules that regulate gene expression using conformation change, affected by binding of small molecule ligands. Although a number of ligand‐bound aptamer complex structures have been solved, it is important to know ligand‐free conformations of the aptamers in order to understand the mechanism of specific binding by ligands. In this paper, we use dynamics simulations on a series of models to characterize the ligand‐free and ligand‐bound aptamer domain of the c‐di‐GMP class I (GEMM‐I) riboswitch. The results revealed that the ligand‐free aptamer has a stable state with a folded P2 and P3 helix, an unfolded P1 helix and open binding pocket. The first Mg ions binding to the aptamer is structurally favorable for the successive c‐di‐GMP binding. The P1 helix forms when c‐di‐GMP is successive bound. Three key junctions J1/2, J2/3 and J1/3 in the GEMM‐I riboswitch contributing to the formation of P1 helix have been found. The binding of the c‐di‐GMP ligand to the GEMM‐I riboswitch induces the riboswitch's regulation through the direct allosteric communication network in GEMM‐I riboswitch from the c‐di‐GMP binding sites in the J1/2 and J1/3 junctions to the P1 helix, the indirect ones from those in the J2/3 and P2 communicating to P1 helix via the J1/2 and J1/3 media. Abstract : The molecular dynamics simulations on a series of models to characterize the ligand‐free and ligand‐bound aptamer domain of the c‐di‐GMP class I (GEMM‐I) riboswitch. The results revealed that the ligand‐free aptamer has an unfolded P1 helix and open binding pocket. The first Mg ions binding to the aptamer is structurally favorable for the successive c‐di‐GMP binding. The P1 helix forms when c‐di‐GMP is successive bound.